Strategic planning for the sustainable tourism development of the Pastaza canton - Carrera Mora, Gabriela Natalia; Oviedo Costales, María Soledad (Tierra Infinita, 2022)
This research evidences the implementation of strategic planning for the promotion of local sustainable tourism development through the implementation of a tourism plan in the Pastaza canton from 2022 to 2027, which constitutes the roadmap for facilitate municipal tourism management, the empowerment of authorities and the strengthening of the coordination and articulation of publicprivate actions in favor of tourism activity. The tourism planning and management instrument is aligned with national planning and is based on current legal regulations, after having assumed the powers from the central government. It was built through the application of qualitative and quantitative methods in the territory with the participation and consensus of actors in the sector; it determines the actions to be carried out through strategic axes in an organized and compatible way with the versatile requirements of demand, supply and local identity.
Keywords: Strategic planning; development; tourism; sustainable; Pastaza